Reliability and Validity of a Nepali-language Version of the Hospital Anxiety and Depression Scale (HADS) - Risal, A.; Manandhar, K.; Linde, M; Koju, R.; Steiner, T.J.; Holen, A. (Kathmandu University Medical Journal, 2017)
Background In several languages and settings, the Hospital Anxiety and Depression Scale (HADS) has demonstrated reliable and valid screening properties in psychiatry. Objective To develop a Nepali version of HADS with acceptable reliability and construct validity for use among hospital patients and in the general population. Method The original English version was translated into Nepali using a forward-backward translation protocol. Psychometric properties were tested by factor analysis and Cronbach’s alpha. The translated scale was administered to three groups of adult in-patients in a university hospital in three trials, and to a sample of adults from the community in a fourth trial. Some of the 14 items were reworded reiteratively to achieve viable semantic and statistical solutions. Results The two-factor solution with anxiety and depression subscales eventually explained 40.3% of the total variance. Cronbach’s alpha was 0.76 for anxiety (HADS-A) and 0.68 for depression (HADS-D). All seven HADS-A items showed at least acceptable item-to-factor correlations (range 0.44-0.74), and full construct validity was achieved for this subscale. Item-to-factor correlations for six HADS-D items were also at least acceptable (range 0.42-0.70); one item (D4) had persistently low correlations throughout all trials, although construct validity was still satisfactory. Conclusion Reiterated rewording of items guided by statistical testing resulted in a Nepali version of HADS with satisfactory psychometric properties.